2020
DOI: 10.1002/cnma.202000394
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Single‐Atom Ruthenium Anchored on Beta Zeolite as an Efficient Heterogeneous Catalyst for Styrene Epoxidation

Abstract: Exploring high‐performance styrene epoxidation catalysts is of great significance. However, it still remains a challenge to synthesize heterogeneous catalysts that simultaneously possess excellent styrene activity and styrene oxide selectivity. Herein, we report a heterogeneous isolated single‐atom Ru supported on microporous Beta zeolite (Ru1/Beta) catalyst fabricated by a wet impregnation method. We reveal that the extraframework AlOH groups on Beta zeolite are responsible for anchoring Ru species, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…However, this Au nanocluster catalyst used an organic oxidant, tert -butyl hydroperoxide, which is less environmentally friendly than our catalyst that uses H 2 O 2 as the oxidant. In addition, our nanosheet catalyst achieved a turnover frequency value of >280 h –1 that rivals the recently reported isolated single-atom Ru catalyst supported on the Lewis acid site of Beta zeolite . Meanwhile, a TOF value comparison of our Al 2 O 3 –FeO x catalysts with different Fe loading in Table S3 suggested that 4%-Al 2 O 3 –FeO x exhibited the highest TOF value (476 h –1 ) at 70 °C among those catalysts.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…However, this Au nanocluster catalyst used an organic oxidant, tert -butyl hydroperoxide, which is less environmentally friendly than our catalyst that uses H 2 O 2 as the oxidant. In addition, our nanosheet catalyst achieved a turnover frequency value of >280 h –1 that rivals the recently reported isolated single-atom Ru catalyst supported on the Lewis acid site of Beta zeolite . Meanwhile, a TOF value comparison of our Al 2 O 3 –FeO x catalysts with different Fe loading in Table S3 suggested that 4%-Al 2 O 3 –FeO x exhibited the highest TOF value (476 h –1 ) at 70 °C among those catalysts.…”
Section: Resultssupporting
confidence: 51%
“…In addition, our nanosheet catalyst achieved a turnover frequency value of >280 h −1 that rivals the recently reported isolated single-atom Ru catalyst supported on the Lewis acid site of Beta zeolite. 70 Meanwhile, a TOF value comparison of our Al 2 O 3 −FeO x catalysts with different Fe loading in Table S3 suggested that 4%-Al 2 O 3 −FeO x exhibited the highest TOF value (476 h −1 ) at 70 °C among those catalysts. Even though 6%-Al 2 O 3 −FeO x contributed the best performance in terms of conversion and selectivity toward styrene oxide, the loss of its atomic efficiency is unavoidable as the size of the FeO x clusters increase, giving a TOF value of 280 h −1 .…”
Section: ■ Introductionmentioning
confidence: 86%
“…An UV-Vis Spectrometer (UV-3600plus, Shimadzu, Japan) was used to record solid UV/Vis-NIR data. The conversion of styrene and selectivity of styrene oxide were analyzed on a PANNA A91Plus Gas chromatography (China) with a capillary column (HP-5 column, 30 m × 0.32 mm, 0.50 μm film thicknesses), using normalization method [Equations ( 6), (7), (8)]:…”
Section: Characterizationmentioning
confidence: 99%
“…[4] To overcome these drawbacks, synthesis of styrene oxide through directly epoxidation of styrene using environmental-begin oxidants is therefore necessary. Among them, heterogeneous catalysts such as nitrides, [5] single-atomicsite catalysts [6][7][8] and others [9,10] have been proposed as promising alternatives for their good oxidation activity and recyclable nature. These studies using hydrogen peroxide or TBHP as oxidants have made excellent progress in the exploring the highly efficient catalytic systems for epoxidation of styrene, [11,12] which always leading to the over-oxidation of styrene to aldehydes or acids.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Furthermore, ruthenium-based zeolites have been used in a variety of catalytic reactions from the epoxidation of styrene, conversion of glucose and sorbitol to glycols and ammonia synthesis. [28][29][30] Also, the activity of Ru catalysts has been documented in the direct amination of alcohols to produce primary amines. 24 Consequently, we explored the use of Ru-zeolites in the catalytic amination of lactic acid to form alanine, an amino acid with application in the biosynthesis of proteins and compared their activity to commercially available Ru catalysts.…”
Section: Introductionmentioning
confidence: 99%